Book Review - Scott, James C.; EI-Khawas, M. A.; B. Cohen (Tufts Archival Research Center, 2005)
Volume 2, Issue 1. Winter. The Moral Economy of the Peasant: Rebellion and Subsistence in Southeast Asia. National Security Memorandum 39: The Kissinger Study of Southern Africa. Book Review